Innovative Economic Development of Uzbekistan: Trends and Prospects - Usmanova Nasiba (Peerian Journals Publishing, 2022)
The article provides detailed information on the innovative economy and economic potential of Uzbekistan. There are also thoughts on innovative economic development. There are also a number of analyzes of the factors affecting the innovative economy of Uzbekistan.
Keywords: innovative economy; economic potential; innovative economic development